Normalized Isometric Shoulder Strength as a Predictor of Ball Velocity in Youth Baseball Players - Amanda J Arnold; Charles A Thigpen; Paul F Beattie; Stacy L Fritz; Michael J Kissenberth; John M Tokish; Ellen Shanley (International Journal of Sports Physical Therapy)
# BACKGROUND